An Implementation of Internship Program to Enhance Teaching Experience for Learners in Schools - Purba, Igna Mariana; Rahmawati, Rahmawati; Herman, Herman; Manihuruk, Leonita Maria Efipanias; Saragih, Mery Chris Isabella; Silaban, Desi Crismas; Sianturi, Eduardo; Rambe, Kartina Rahmadhani; Bangun, Bangun; Munthe, Bangun; Sirait, Tumpal Richardo (AMK : Abdi Masyarakat UIKA, 2025)
This paper explores a school implemented twelve-week full-time internship subject designed to enhance preservice primary teachers first experiential placement at school. This subject is specifically focused on preparing preservice teachers through orientating them in key facets of a school, thereafter contextualizing the theory studied at University within classroom practice, and ultimately developing further competencies in their teaching and learning methodology. Three stages of activities were implemented by the authors to compile the activity report which includes the Preparation phase, Implementation and Evaluation phase. The program was designed to be cumulative in nature, building on the learning, practice and reflection developed in the previous week and learning activities will be scaffolded to incorporate both independent and collaborative and peer learning. The results showed that an implementation of an internship experience improved a sense of readiness of intern teachers, confidence in classroom management, and general teaching ability. Although well-supported as a critical experience, internships take considerable time and effort to organize and execute. Measures of quality support the need for an intense focus during the internship.